Clinical efficacy and biomechanical analysis of a novel hollow pedicle screw combined with kyphoplasty for the treatment of Kümmell disease - Shixiao Zhong; Hui Zhong; Kun Huang; Yayu Zhao; Wen Lei; Weichao Li (JOR Spine)
Abstract Background Vertebral augmentation is the preferred treatment for Kümmell disease (KD), but there exists a risk of cement displacement resulting in severe back pain and exacerbation of kyphosis. The study aimed to investigate the efficacy and safety of a novel hollow pedicle screw combined with kyphoplasty (HPS‐KP) for treating KD, effectively preventing postoperative bone cement displacement. Methods The prospective study included 50 KD patients with no neurological deficit detected during clinical and radiological evaluation who underwent HPS‐KP (n = 25) and PKP (n = 25) surgeries. The visual analogue scale (VAS) score, Oswestry dysfunction index (ODI), anterior vertebral height (AVH), wedge‐shape affected vertebral Cobb angle (WCA), bisegmental Cobb angle (BCA), and complications were evaluated and compared in both groups. Besides, a finite element (FE) model of T11‐L2 was constructed. The stress distributions, maximum von Mises stresses of vertebrae and bone cement, and maximum displacement of bone cement were compared and analyzed. Results The VAS and ODI scores at 3 days, 3 and 6 months, and 1 year after surgery significantly improved in both groups (p < 0.05). The AVH, BCA, and WCA significantly improved initially after the surgery in both groups (p < 0.05). The displacement of M2 was larger than other models, especially in flexion, right bending, and left and right rotation, while that of M6 was the lowest under all conditions. Conclusion HPS‐KP was a safe and effective treatment for KD, effectively relieving pain, restoring vertebral height, and correcting local kyphosis, and it had better biomechanical stability and safety than ordinary single PKP and PKP combined with pediculoplasty in avoiding cement loosening and displacement.